Capacidad antioxidante de la pulpa (Ananas comosus) piña y elaboración de compota fortificada - Vásquez Ravines, Alices Lucero (2024)
This research work was carried out in the facilities of the Amazon Natural Resources Research Center (CIRNA), and the Pilot Plant Facilities – of the National University of the Peruvian Amazon (U.N.A.P), consisting of two sections in the research, the first was to find mu determine the antioxidant capacity of pineapple pulp (Ananas comosus), variety Cayenne lisa, for this we worked using the determinative methods of DPPH, ABTS and method of determination of total phenols, for which absorbance readings were used: 515, 734 and 725 nm, in dilutions (7:10, 4:10, 2: 10 and 0.6:10, giving an average expressed in μmol / TE: 1.904, 5.098, 6.180 and 12.175, having a percentage of inhibition of 40.52, 67.13, 45.52 and 31.57. by the DPPH method, and by the ABTS method: 26.82, 40.77, 68.14, 178.52 expressed in μmol/TE/100 g. dry sample, and total phenol content expressed in mg/100 grams. In the second stage of the it became compote, for which a standard formulation and diagram was followed, using pineapple pulp, maltrodextrin, white sugar, potassium sorbate and vitamin / mineral mix, being the diagram: raw material, reception, washing / disinfection, selection, peeling / cutting, blanching, pulping, formulation, cooking, homogenization, pasteurization, packaging, sealing / vacuum, sterilization, cooling and storage, giving results of physical-chemical analyses F1, F2, F3: moisture 74.00, 73.72, 73.60, ash: 0.43, 0.40, 0.40, fat: 0.50, 0.52, 0.53, protein: 0.79, 0.87, 0.80, carbohydrates: 24.28, 24.48, 24.50, titratable acidity: 0.70, 0.77, 0.78, pH(20oC): 4.67, 4.60 and 4.68, Calories: 104.78, 106.08 and 105.97, dry matter: 26.00, 26.28 and 26.40, in reference to the microbiological results fungi were: <10, <10, <10 and yeasts: 5, <10, 5 all within the quality ranges required by the MINSA-NTP-591-2008, in reference to sensory analysis formulation 3 is the one that had the best evaluation by the 25 semi-trained panelists, and finally in the statistical evaluation there are no significant differences between each formulation.